TEACHERS’ PERSPECTIVES ON PROFESSIONAL ETHICS - Kumar, Sunil; Kushwaha, Rajlakshmi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This research paper attempts to study school teachers’ perspectives on the professional ethics required of them. The authors mainly studied the awareness and understanding of teachers on some essential professional ethics. It has been found that teachers are confronted with many moral issues while discharging their responsibilities and in decision-making. The paper’s significant findings highlighted the need for a professional code of conduct for teachers considering policy perspectives that guide them in discharging their duties as teachers. The paper highlighted the need to incorporate the ethics curriculum in pre-service and in-service teacher education programmes, which is essential to empower them and support them to understand their role as professionals. The study further emphasises the need to develop a framework on professional ethics for teachers and use the developed framework during their professional development programmes at different levels.